Performance Analysis of Traction Synchronous Machine With Rotor Field Winding and Two-Phase Harmonic Field Exciter With PWM Supply - Vladimir Dmitrievskii; Vadim Kazakbaev; Vladimir Prakht; Aleksey Paramonov; Victor Goman (IEEE Access, 2025)
In contemporary automotive, maritime, and commercial vehicle technology, various types of transport rely on permanent magnet synchronous motors for their space-saving advantages. However, these motors come with certain drawbacks. Permanent magnets, while efficient, can prove costly and have issues maintaining consistent flux, especially when requiring wide constant power speed ranges in the field weakening domain. Consequently, an appealing substitute for permanent magnet motor systems might involve motors that incorporate a field winding, offering potential benefits in terms of both cost and performance adaptability. The article presents a new design of a traction synchronous motor with a field winding on the rotor with a two-phase brushless harmonic exciter that increases the electromotive force on the field winding. This article also proposes a zero-sequence current injector circuit using only the lower transistor, which does not require an expensive upper driver. Its mathematical model is proposed considering PWM and the simulation results are presented. The operation of the motor with relay control of the excitation flux is considered.